Pengaruh Persepsi Risiko dan Kepercayaan Konsumen terhadap Keputusan Pembelian pada Tokopedia (Studi Kasus pada Mahasiswa Universitas Negeri Padang) - Rezka Rahmadita; Rose Rahmidani (Jurnal Salingka Nagari, 2023)
The study's goal was to see how risk perception and consumer trust affected purchasing decisions at Tokopedia among Universitas Negeri Padang students. This type of study is causal. The participants in this study were students at Universitas Negeri Padang. Non-probability sampling with purposive sampling technique was used in this study, and the number of samples was determined using the Cochran formula to be as many as 97. The data used is primary data obtained by distributing questionnaires to Universitas Negeri Padang students who meet certain criteria, namely Universitas Negeri Padang students who have made purchases on Tokopedia. Multiple regression analysis with SPSS 22 was used as the analytical method. According to the findings of this study, 1) risk perception and consumer trust have a significant effect on purchasing decisions at Tokopedia among Universitas Negeri Padang students, 2) risk perceptions have a positive and significant effect on purchasing decisions at Tokopedia among Universitas Negeri Padang students, and 3) consumer trust has a positive and significant effect on purchasing decisions. Universitas Negeri Padang students have a significant influence on Tokopedia purchasing decisions.